PENGARUH UKURAN PERUSAHAAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yonson Pane (LP2MTBM MAKARIOZ, 2018)
This study aims to determine the effect of company size / natural total asset logarithms and previous year's audit opinion on going-concern audit opinions partially and simultaneously on textile and garment companies listed on the Indonesia Stock Exchange (IDX).This study uses a type of quantitative data and data sources are secondary data. The unit of analysis and observation in this study were textile and garment companies listed on the IDX with a population of 19 companies. From the population, chosen by purposive sampling technique and obtained as many as 70 samples consisting of 14 companies for 5 periods, namely the period 2012-2016. The analytical method used is logistic regression analysis.The results of the study partially show that the size of the company has a significant value of 0.879> 0.05 and the previous year's audit opinion has a significant value of 0.000 <0.05. The results of the study simultaneously indicate the size of the company and previous year's audit opinion has a significant value of 0.000 <0.05. The coefficient of determination (Nagelkerke R Square) is 0.791 or 79.1%, which means that the going concern audit opinion variable can be explained by the variable size of the company and the previous year's audit opinion.